Analysis of Village Revenue and Expenditure Budget Management - Ningsih, Eka Amiati; Ghafur, Abd; Norhayati, Norhayati (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
The era of globalization, development phenomena are described in increasingly complex problems. The management of Village Revenue and Expenditure Budget (Anggaran Pendapatan dan Belanja Desa/ABDes) in Jurang Jero Village, Gading District, Probolinggo Regency has been implemented in accordance with the budget management mechanism, from the preparation stage, assessment stage, alternative activity planning stage (planning), action plan formulation stage, activity implementation stage (implementation), Evaluation stage and termination stage. And there are also factors that hamper Village APBDes Management in the Village, namely the difficulty of unifying Perceptions Regarding Budget Use, Reporting Systems and Disbursement Mechanisms which are influenced by the quality of Human Resources. APBDes Management Efforts are to Unify Perceptions Regarding Budget Use, Reporting Systems and Disbursement Mechanisms. In this way, the inhibiting factors in APBDes Management in Jurang Jero Village, Gading District, Probolinggo Regency, have been resolved. The type of research used in this research is qualitative descriptive research. Data collection techniques using interview techniques and interview guides were used only in the form of an outline of the problem. Assessment of alternative activity planning stages (planning), action plan formulation stage (formulation action plan), implementation stage, evaluation stage, and termination stage. The inhibiting factor in managing the Village Budget and Expenditures in Jurang Jero Village, Gading District, Probolinggo Regency is the difficulty of unifying perceptions regarding the use of budgets and reporting systems, as well as disbursement mechanisms.